A sharp skirt notch filter based feedforward 3rd harmonic cancellation scheme for ultra‐high frequency wireless communication system in 834–879 MHz. Issue 4 (April 2016) - Jung, Won‐Jae; Jung, Jin‐Woo; Jang, Peter; Park, Jun‐Seok
ABSTRACT: This article presents a feedforward 3rd harmonic cancellation scheme for ultra‐high frequency (UHF) wireless communication system in 834–879 MHz. The major features are highlighted: a special notch filter with sharp skirt performance (e.g., both lower and higher band edge from 834 to 879 MHz yield lower than −40 dB cutoff), and micro‐controller based amplitude/phase control on feedforward path signal generation for fine harmonic cancellation. A prototype was implemented; it works out 47.36 dB Hz −1 cut‐off and 60 dBc ACLR. © 2016 Wiley Periodicals, Inc. Microwave Opt Technol Lett 58:1006–1010, 2016